Pengaruh Lingkungan Kerja Fisik dan Disiplin Kerja Terhadap Kinerja Karyawan Bank Perkreditan Rakyat (BPR) Bank Daerah Kota Madiun - Dhiyan Septa Wihara (Jurnal Ilmiah Aset, 2017)
This research have a purpose (1) to analyze the influence of physical working ebnvironment depend on bank employee perfomance BPR “Rural Bank” in madiun city (2) to analyze the influence of job discipline depend on the bank employee performance BPR “Rural Bank” in madiun city (3) to analyze the influence of physical working environment and job discipline depend on the bank employee performance BPR”Rural Bank” in Madiun city. The kind of this research is explanatory research with quantitative approach. The sample of this research is the bank employee of BPR”Rural Bank” in Madiun city number in 50 bank employee with sampling technique using purposive sampling. The data collected using quistionary. The data that the researcher get to be analyze using multiple regresion analyze, Simultaneous (F-test) and Partial(t-test). The result on the research show that the physical environment and job discipline in simultaneous give significant influence depend on bank employee BPR”Rural Bank” in madiun city with significant score 0,000 (p<0.05). This score show that the physical working environment in partial does not giving significant influence depend on the bank employee performance BPR”Rural bank” in madiun city. In line the result of test partial also not give an effect to the bank employee perfomance BPR”Rural bank” in Madiun city. The t-test show the score 0,116 on the other hand. The job discipline bank employee BPR”Rural bank” in Madiun city, show the score with score significant t-test 0,000.